2022
DOI: 10.3389/fpsyg.2021.767363
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality-Integrated Immersion-Based Teaching to English Language Learning Outcome

Abstract: Globalization and informatization are reshaping human life and social behaviors. The purpose is to explore the worldwide strategies to cultivate international talents with a global vision. As a global language with the largest population, English, and especially its learning effect, have always been the major concerns of scholars and educators. This work innovatively studies the combination of immersion-based English teaching with virtual reality (VR) technology. Then, based on the experimental design mode, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…(2022) An innovative affective mobile language tutoring system (AMLTS) To use AMLTS in an effective manner 63 Taiwanese students learn Japanese AMLTS emotional interaction design significantly promotes learner engagement and performance Xie et al. (2019) Open-domain dialog systems To employ a multi-turn chatbot with the goal of learning and creating emotional reactions that humans are now capable of 4 participants The chatbot monitors the discussion environment and provides replies that are more emotionally suitable while doing similarly well on grammar Xie et al. (2021) Virtual reality (VR) technology To mix immersion-based English instruction with VR technology in order to increase learning results 106 Chinese Students The findings indicated that students enjoyed exploring English culture and appreciating its history and customs Zhang (2021) CNN interactive agent The research offers a convolutional neural network-based method for recognizing how learners' attention, memory, reasoning N/A This research facilitates the realization of harmonious emotional contact in the innovative learning environment in real-time and without disrupting the learners' usual online learning …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2022) An innovative affective mobile language tutoring system (AMLTS) To use AMLTS in an effective manner 63 Taiwanese students learn Japanese AMLTS emotional interaction design significantly promotes learner engagement and performance Xie et al. (2019) Open-domain dialog systems To employ a multi-turn chatbot with the goal of learning and creating emotional reactions that humans are now capable of 4 participants The chatbot monitors the discussion environment and provides replies that are more emotionally suitable while doing similarly well on grammar Xie et al. (2021) Virtual reality (VR) technology To mix immersion-based English instruction with VR technology in order to increase learning results 106 Chinese Students The findings indicated that students enjoyed exploring English culture and appreciating its history and customs Zhang (2021) CNN interactive agent The research offers a convolutional neural network-based method for recognizing how learners' attention, memory, reasoning N/A This research facilitates the realization of harmonious emotional contact in the innovative learning environment in real-time and without disrupting the learners' usual online learning …”
Section: Resultsmentioning
confidence: 99%
“…(2022) Ellie Ellie's utterances are also culture-coded (as someone who grew up in San Francisco, California, in the United States) Mageira et al. (2022) AsasaraBot is introduced to the students as the Goddess of Snakes cultural content learning Wahyuni (2022) An EFL chatbot The culture embedded in the target language Xie et al. (2021) VR technology English culture Freidkin and Ksenofontova (2021) Telegram-bot “Pardes” Israel culture - Geographical position of Israel.” Safitri et al.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the emergence of digital platforms and online resources has revolutionized the landscape of English teaching, offering diverse avenues for interactive learning and personalized instruction. As universities continue to adapt and evolve their English teaching practices, the goal remains consistent: to empower students with the language skills and cultural competence necessary for success in an increasingly interconnected world [3].…”
Section: Introductionmentioning
confidence: 99%
“…This approach leverages data-driven insights and gaming mechanics to engage learners and promote active participation. Studies byXie et al (2022) and Liu & Zou (2022) provide empirical evidence supporting the effectiveness of immersion-based VR approaches for language learning. Immersive experiences in virtual environments facilitate authentic language practice and engagement, contributing to improved proficiency.…”
mentioning
confidence: 97%
“…The design and optimization of an English speaking teaching model using VR technology offer a compelling approach to language learning [8]. By providing immersive, interactive, and personalized experiences, the model holds the potential to revolutionize how English proficiency is acquired and mastered.…”
Section: Introductionmentioning
confidence: 99%